Challenges and opportunities for survival entrepreneurs in the township of Soweto - Molapo, Refilwe (University of the Witwatersrand, Johannesburg, 2024)
This research paper investigated the challenges and opportunities of survivalist entrepreneurs in Soweto by evaluating the effectiveness of the entrepreneurial ecosystem. The study also examined the potential of using education to improve the entrepreneurial mindset. Additionally, the research investigated how education and the entrepreneurial mindset can be leveraged to improve business performance. A positivist paradigm was adopted to guide the quantitative research strategy. A cross-sectional study was conducted, and the data was collected from 125 respondents through a self- administered questionnaire. The population sample was subdivided into smaller groups based on the participant’s geographical location within Soweto, this was done through cluster sampling. Thereafter, the convenience sampling technique based on availability and accessibility was employed to reach the participants within the designated clusters. The hypotheses were evaluated through a single moderated regression model as the conceptual framework perfectly represented a moderated mediation model. The results from the model summary confirmed that all three variables – entrepreneurial mindset, entrepreneurial education, and entrepreneurial ecosystem – significantly influenced business performance. The direct effects of the entrepreneurial ecosystem on the entrepreneurial mindset were confirmed to be significant. Furthermore, the research demonstrated that the entrepreneurial mindset mediated the relationship between the entrepreneurial ecosystem and business performance in the township of Soweto. The practical implications of the study are that further investment in developing the resources and strengthening the support infrastructure in the township of Soweto will create more opportunities for survivalist entrepreneurs to improve their business performance. The study revealed that those with increased education levels are not immune from the systemic challenges that may cause individuals to start informal businesses in the township. Therefore, creating educational programmes that focus on developing practical skills could have a positive effect, empowering these survivalist entrepreneurs with the necessary skills to improve their business performance.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: survivalist entrepreneur; Entrepreneurial ecosystem; Entrepreneurial mindset; UCTD; SDG-8: Decent work and economic growth